Novel temporary endodontic medication based on calcium silicate strategy: a biological and physicochemical study - El Hachem, Claire; Sauro, Salvatore; Eid, Ammar; Arıcan, Burçin; Alrayesse, Raya; Fabro, Camille; Gribova, Varvara; Hardan, Louis; Haikel, Youssef; Kharouf, Naji (Frontiers in Dental Medicine, 2024)
Introduction The purpose of this in vitro study was to compare the physicochemical and biological properties of a traditional calcium hydroxide-based cement (Cal) to a novel endodontic material based on calcium silicate strategy in premixed formulation (Bio-C). Methods Crystalline structure evaluation and pH analysis were performed at different time periods (3–168 h). Contact angle, surface roughness, solubility and flowability of both materials were also investigated. The antibacterial activity of each material was assessed using a direct contact test against Enterococcus faecalis (E.faecalis), and the cytotoxicity was performed by using periodontal ligament cells. Statistical analysis was accomplished using one-way analysis of variance and Kruskal-Wallis tests. Results An alkaline pH was observed in both the tested materials. Higher pH values were attained in Cal compared to Bio-C (p < 0.05). Higher flowability, solubility and wettability were attained for Bio-C compared to Cal (p < 0.05). Crystalline structures were observed on the surface of Bio-C after immersion in PBS (168 h). Cal presented higher antibacterial activity compared to Bio-C against E.faecalis. Only undiluted Bio-C extracts demonstrated slight cytotoxicity, while all the other tested specimens had no cytotoxicity. Discussion In conclusion, the novel bioceramic medication might be used as a suitable alternative agent to the traditional calcium hydroxide cements due to its biological and physicochemical properties. However, further studies on the ability of removing Bio-C from root canal are required to determine whether such a temporary bioceramic can ameliorate root canal treatments.